How Masks Work, Or Masks Work How? - Young-Laughlin, Judi (Journal of ritual studies, 1988)
Masking is ubiquitous to the culture areas of the world and is a symbolic activity inextricably associated cross-culturally with cosmological drama and shamanic ritual. Our question is, "Masks work how?" In Part 1, we place masks within their physical, cultural and cosmological context so as to view the activity of masking as part of a wider symbolic process. Masks are seen to be transformations of face. In Part 2, the work of masking is realized as a transformation of experience, and is related to a general cycle of meaning in culture whereby cosmological beliefs give rise to direct experience, and experience verifies and vivifies cosmology. And in Part 3 the "how" of masking is explained using a biogenetic structural perspective which traces the possible transformations of brain that may occur within the wearer and audience and that may mediate a variety of mask-related experiences.